TRANSRADIAL ACCESS TO TREATMENT OF PATIENTS WITH ACS: STILL TRAINING OR ALREADY ROUTINE PRACTICE? - V V Majskov (RUDN Journal of Medicine, 2017)
The article is devoted to the study of a one-center experience of routine application of transradial access (TRD) by default in the treatment of patients with ACS in a short-term clinic, which has neither a vascular or cardiovascular surgery department. The experience of treatment of 3436 patients with acute coronary syndrome was analyzed, of which 72.64% were patients with acute myocardial infarc-tion. The use of TRD was considered successful in the case of completion of the procedure of stenting through the arm without the need for conversion of arterial access to the thigh. By default, right transradial access was used, except for cases of known anamnesis of mammarocoronary shunting. Time for puncture of the radial artery, installation of the introducer and catheterization of the arch of the aorta was 2.8 - 1.1 min. The average duration of fluoroscopy was 13.36 ± 8.86 minutes. The immediate success of the intervention, performed by transradial access, was 98%, of which the need for conversion to contralateral access was in 6.5% of patients. In total, two patients developed access point hematomas, which required the transfusion of blood components, managed to stop bleeding conservatively, in no case did vascular surgeons need help.